Hypercapnic Ventilatory Response in the Weaning of Patients with Prolonged Mechanical Ventilation. (30th October 2017) - Lee, Chung-Shu; Chen, Ning-Hung; Chuang, Li-Pang; Chang, Chih-Hao; Li, Li-Fu; Lin, Shih-Wei; Huang, Hsiung-Ying
Abstract : Objective . To investigate whether hypercapnic ventilatory response (defined as the ratio of the change in minute ventilation [Δ V ˙ E ] to the change in end-tidal partial pressure of carbon dioxide [Δ P E T C O 2 ]) is a predictor of successful weaning in patients with prolonged mechanical ventilation (PMV) and to determine a reference value for clinical use. Methods . A hypercapnic challenge test was performed on 32 PMV subjects (average age: 74.3 years ± 14.9 years). The subjects were divided into two groups (i.e., weaning successes and weaning failures) and their hypercapnic ventilatory responses were compared. Results . PMV subjects had an overall weaning rate of 68.8%. The weaning-success and weaning-failure groups had hypercapnic ventilatory responses (Δ V ˙ E / Δ P E T C O 2 ) of 0.40 ± 0.16 and 0.28 ± 0.12 L/min/mmHg, respectively (P = . 036 ). The area under the receiver operating characteristic curve was 0.716 of the hypercapnic ventilatory response, and the practical hypercapnic ventilatory response cut-off point for successful weaning was 0.265 with 86.4% sensitivity and 50% specificity. Conclusions . PMV subjects who failed weaning had a lower hypercapnic ventilatory response than successfully weaned subjects. However, the prediction capacity of this test, assessed by the area under the receiver operating characteristic (ROC) curve, poorly predicted weaning outcome.